Pendekatan Kontekstual dalam Pendidikan Jasmani - Sri Winarni (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2005)
Curriculum of 2004 that is called a Competence-based Curriculum demandsfor all subject lessons to apply a learning approach which is capable to strive for thedevelopment of student’s ability in managing the learning acquirements (competency)that is in appropriate with each condition. Thereby, the learning process will be moreconcerned about how students learn than what they learn. Curriculum of 2004 placesstudents as educated subjects, that is, involves students in the course of learning moreoften. This approach is derived from an assumption that students possess potencies tothink by themselves, and those potencies can only be realized as long as they aregiven a lot of opportunity to think by themselves.Contextual approach (Contextual Teaching and Learning/ CTL) is a concept of learning,assistive to teachers in correlating between matters that they teach and situations ofthe real world of students, and in pushing students to make a relation for knowledgethey already have with its applications in their life as members of family and society, byentangling six principal components of effective learning, that are: Constructivism,Questioning, Inquiring, Learning Community, Modeling, and Authentic Assessment. AStudy of physical education using contextual approach is expected to assist in reachingtargets of physical education. Physical move experiences obtained by students areexpected, not because of following the example of or imitating teachers, but becauseof students find their own move patterns through teachers’ guidance/ facility.Keyword: Curriculum, Contextual Approach, Physical Education